Inovasi Manajerial Kepala Madrasah dalam Peningkatan Mutu Pembelajaran di MIS Miftahul Hasanah Muhammadiyah Songing Kabupaten Sinjai - Muallim; Fahmi Surya Abdi (Sumule Indonesia Publishing, 2025)
This study examined the managerial innovations of the madrasah principal at MIS Miftahul Hasanah Muhammadiyah Songing to improve learning quality. Using a qualitative–descriptive design, data were gathered through interviews, classroom observations, and documentation, and analyzed using thematic analysis with source triangulation. The findings showed that managerial innovations were realised through collaborative work planning, effective communication, discipline modelling, and teacher capacity-building via Teachers’ Working Groups (KKG), training, facility provision, and follow-up supervisory coaching. However, challenges remained in optimizing instructional delivery and resource use, particularly due to limited ICT support. The study concluded that effective managerial leadership is crucial for aligning goals, enhancing teacher competence, and improving the learning environment. Sustaining gains requires more consistent implementation alongside targeted infrastructure support.